Deep venous thrombosis after major abdominal surgery in a Ugandan hospital: a prospective study - Muleledhu, Andrew L.; Galukande, Moses; Makobore, Patson; Mwambu, Tom (International journal of emergency medicine, 2013)
Deep venous thrombosis (DVT) is a major cause of morbidity and mortality among postoperative patients. Its incidence has been reported to range between 16% and 38% among general surgery patients and may be as high as 60% among orthopaedic patients. The most important clinical outcome of DVT is pulmonary embolism, which causes about 10% of hospital deaths. In over 90% of patients, occurrence of DVT is silent and presents no symptoms until onset of pulmonary embolism and/or sudden death. The only effective way of guarding against this fatal condition is therefore prevention/prophylaxis. However, prophylaxis programs are usually based on the estimated prevalence of DVT in that particular community. There is currently no data concerning rates of postoperative DVT in Uganda. The purpose of the study was therefore to determine the prevalence of DVT among postoperative patients at Mulago Uganda’s National Referral Hospital. Methods: A cross sectional descriptive study was conducted between March and June 2011. Eligible patients were identified and screened and patient details were collected. Clinical examinations were done on postoperative days (PODs) 1, 2, and 4 and Doppler ultrasounds were done on POD 7 and POD 21 to assess for DVT. Patients found with DVT were treated appropriately according to local treatment guidelines. Results: A total of 82 patients were recruited, 4/82 (5%) had DVT. The most common risk factor was cancer. The overall mean age was 45 years (range 20–83 years). The male to female ratio was 1.6:1. Participants with more than one risk factor for DVT were 16/82 (20%). Conclusions: Prevalence of DVT among major post-abdominal surgery patients was low (5%). Cancer was the most common associated factor apart from surgery.
Keywords: Deep venous thrombosis; Duplex Doppler ultrasound; Postoperative; Sub-Saharan Africa